Backbone 1H, 13C, and 15N resonance assignments of the N-terminal domain of FKBP38 (FKBP38NTD) - Kang, Cong Bao (2012)
FK-506 binding protein 38 (FKBP38) interacts with Bcl-2/Bcl-Xl and helps them localize at the mitochondrial